Intersectionality and the hidden patriarchy in Rowling’s Harry Potter and the Deathly Hallows - Qothrunnada, Atik; Istiani, Imas (Universitas Islam Sultan Agung, 2025)
This study explores intersectional identities in female characters to investigate hidden patriarchy in Rowling’s Harry Potter and the Deathly Hallows. This study aims to explore the intersectional identities of female characters and how they expose the hidden patriarchal structures within the narrative. Using a qualitative descriptive approach with textual analysis applied to selected female characters as primary data, this study used Crenshaw’s intersectional feminist lens to explore how overlapping identities affect equality in society. The findings of this study uncover the female characters only function as supporters, enforcers, or extensions of male authority. It highlights that the female characters experience overlapping oppression and are positioned in a male-dominated hierarchy. The conclusion of this study proves that the existence of hidden patriarchy in the narrative is revealed through the lens of intersectionality which clarifies gender-based boundaries. It is recommended that further discussions and critical analyses be conducted to challenge patriarchal narratives in popular literature, as literary representations continue to reflect and reinforce societal norms.